Gemcitabine and doxorubicin in immunostimulatory monophosphoryl lipid A liposomes for treating breast cancer. Issue 1 (16th September 2020) - Wu, Debra; Zhao, Zongmin; Kim, Jayoung; Razmi, Amaya; Wang, Lily Li‐Wen; Kapate, Neha; Gao, Yongsheng; Peng, Kevin; Ukidve, Anvay; Mitragotri, Samir
Abstract: Cancer therapy is increasingly shifting toward targeting the tumor immune microenvironment and influencing populations of tumor infiltrating lymphocytes. Breast cancer presents a unique challenge as tumors of the triple‐negative breast cancer subtype employ a multitude of immunosilencing mechanisms that promote immune evasion and rapid growth. Treatment of breast cancer with chemotherapeutics has been shown to induce underlying immunostimulatory responses that can be further amplified with the addition of immune‐modulating agents. Here, we investigate the effects of combining doxorubicin (DOX) and gemcitabine (GEM), two commonly used chemotherapeutics, with monophosphoryl lipid A (MPLA), a clinically used TLR4 adjuvant derived from liposaccharides. MPLA was incorporated into the lipid bilayer of liposomes loaded with a 1:1 molar ratio of DOX and GEM to create an intravenously administered treatment. In vivo studies indicated excellent efficacy of both GEM‐DOX liposomes and GEM‐DOX‐MPLA liposomes against 4T1 tumors. In vitro and in vivo results showed increased dendritic cell expression of CD86 in the presence of liposomes containing chemotherapeutics and MPLA. Despite this, a tumor rechallenge study indicated little effect on tumor growth upon rechallenge, indicating the lack of a long‐term immune response. GEM/DOX/MPLA‐L displayed remarkable control of the primary tumor growth and can be further explored for the treatment of triple‐negative breast cancer with other forms of immunotherapy. Abstract :